Review Pemanfaatan Design Expert untuk Optimasi Komposisi Campuran Minyak Nabati sebagai Bahan Baku Sintesis Biodiesel - Reshita Amalia Ramadhani; Dody Herdian Saputra Riyadi; Bayu Triwibowo; Ratna Dewi Kusumaningtyas (Jurnal Teknik Kimia dan Lingkungan, 2017)
Mixing different types of vegetable oils for synthesis of biodiesel is one of the efforts for renewable alternative energy. Mixed oil of vegetable oils more potential because it is not difficult to finding raw materials and not useful yet. Vegetable oils mixture as raw materials used include: Jatropha curcas oil, nyamplung oil and waste cooking oil. The mixed and optimized compositions use the simplex lattice design method with a total mixture. The data to be obtained is the influence data of each mixed oil to decrease of FFA during esterification reaction. Simplex lattice design method is one of the methods available in the software Design Expert 10.0. The designs used to optimize the formula on different amounts of different material compositions. The biodiesel synthesis is run based on the experimental design produced by the Expert Design 10.0 program. The use of lattice simplex method design: determination formula, optimizing formulation variable and total number of runs, keeping total concentration constant. ANOVA (Analysis of variance) to determine the significance of response analysis among variables and can know the suggested model. Desirability is a method that shows the program's ability to meet the criteria specified in the final product. The desired value that is critical to the desired product improvement program is so perfect.